Effect of Expansive Admixtures on the Shrinkage and Mechanical Properties of High-Performance Fiber-Reinforced Cement Composites - Won-Chang Choi; Hyun-Do Yun (The Scientific World Journal)
High-performance fiber-reinforced cement composites (HPFRCCs) are characterized by strain-hardening and multiple cracking during the inelastic deformation process, but they also develop high shrinkage strain. This study investigates the effects of replacing Portland cement with calcium sulfoaluminate-based expansive admixtures (CSA EXAs) to compensate for the shrinkage and associated mechanical behavior of HPFRCCs. Two types of CSA EXA (CSA-K and CSA-J), each with a different chemical composition, are used in this study. Various replacement ratios (0%, 8%, 10%, 12%, and 14% by weight of cement) of CSA EXA are considered for the design of HPFRCC mixtures reinforced with 1.5% polyethylene (PE) fibers by volume. Mechanical properties, such as shrinkage compensation, compressive strength, flexural strength, and direct tensile strength, of the HPFRCC mixtures are examined. Also, crack width and development are investigated to determine the effects of the EXAs on the performance of the HPFRCC mixtures, and a performance index is used to quantify the performance of mixture. The results indicate that replacements of 10% CSA-K (Type 1) and 8% CSA-J (Type 2) considerably enhance the mechanical properties and reduce shrinkage of HPFRCCs.